Recent African migration to South America : The case of Senegalese in Argentina - Zubrzycki, Bernarda (2012)
African migration to Latin America is new and is made up by mixed migration flow. The arrival of these new migrants appears to agree with the trends identified by international studies about African immigration which refer that, in general, the migratory flows have diversified and become dense, and the migrants have begun to move to non-conventional destinations with which they do not have previous linguistic, cultural or colonial bonds – like the Argentinean case -. This is partly due to the deepening of the economic instability of West Africa between 1980-1990 and the restrictive policies of the EU and USA after September 11th, 2001. Argentina is the most important country of destination for one flow of West Africans, mainly Senegalese, Ghanaians and Nigerians. Specifically, in this article we present a characterization of the Senegalese migration in Argentina with the intention to contribute to the study of this new south-south African migration flow.